Strategi Pembelajaran Inkuiri untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Gep Rianto; Reza Hanafi; Gusmaneli Gusmaneli (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Inquiry learning strategy is an educational approach that places students at the center of the learning process by encouraging them to actively seek, discover, and conclude knowledge through questioning, observing, and critically analyzing. In this strategy, students are not passive recipients of information from the teacher but are directly involved in learning activities that demand critical and analytical thinking skills. Through inquiry learning, students develop critical thinking abilities by engaging in stages such as problem formulation, hypothesis development, data collection, and drawing conclusions based on observations and analysis. This approach has been proven effective in enhancing students’ critical thinking skills as it promotes active and independent participation in learning, while also boosting motivation and self-confidence. The teacher acts as a facilitator who guides and motivates students to sharpen their critical thinking skills in solving problems systematically and logically. Thus, inquiry learning strategy not only enriches students’ understanding of the subject matter but also equips them with essential thinking skills to face future life and learning challenges.